KARAKTERISTIK PERKEMBANGAN ANAK USIA 5-6 TAHUN DALAM ASPEK KOGNITIF MELALUI PERMAINAN BALOK - Mardianingsih, Mardianingsih; Azizah, Nuris (Jurnal Caksana : Pendidikan Anak Usia Dini, 2022)
This study aims to obtain information on the developmental characteristics of children aged 5-6 years in the cognitive aspect through block games at PAUD Al-Mardiyah Mekar Jaya, Pinang District, Tangerang City. PAUD Al-Mardiyah Mekar Jaya is located in the district of Pinang, Tangerang City, Banten Province. Established in 2010 and developing the "Playing Blocks" learning method. The implementation of playing blocks at PAUD Al-Mardiyah Mekar Jaya is generally carried out with various activities that are individual and group. The activities carried out are direct practical activities that focus on the ability of cognitive values in children, besides that they have implemented 10 steps and principles of play for early childhood.